(3JTfja GdSeY, HJYOjO GdSHYs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg aEfj deG QCjJ GdMOjK GdeQSd GdhGQO aj Cf GdehJi jaJfhf aj bHhQge SHYI CjGe CfcQ efcQhf hJYLH eJYLHhf hbGdhG eYG MceI gPG GdYOO adh GSJMi gDdGA de jfcQhG Pdcs
(3BNQgG (B:s
(3hCNQL GHf CHj MGJe Yf GHf YHGS bGd GdOfjG LeYI ef LeY GdBNQI SHYI BdGa SfI (B, (3hCNQL GdMcje aj fhGOQ GdCUhd Yf CHj gQjQI bGd bGd QShd Gddg Udi Gddg Ydjg hSde CWhd GeJj ecKG aj GdfGQ hGdMeO ddgs
(3Vef eLehY Hg QSGdI HNW eWGHb eDQNI (B1124 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\301s
(3cTa GdXfhf (B1\409s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdJUha hGdBOGH GdTQYjIs